Procedimientos para Eutanasia Humanitaria de Ganado Enfermo, Herido y/o Debilitado Poster Sobre Eutanasia en Ganado Bovino - Jan K. Shearer; Paul Nicoletti; Pedro Melendez (EDIS)
VM-157, a full-color wall chart by Jan K. Shearer, Paul Nicoletti and Pedro Melendez, is the Spanish language version of VM-153, "Humane Euthanasia Procedures: For Sick, Injured, and/or Debilitated Livestock Wall Chart." It describes the correct way to humanely euthanize cattle using gunshot or penetrating captive bolt. Published by the UF Department of Veterinary Medicine -- Large Animal Clinical Sciences, April 2007.